2020
DOI: 10.1016/j.mechmachtheory.2020.103843
|View full text |Cite
|
Sign up to set email alerts
|

Predictive capability of various linearization approaches for floating-ring bearings in nonlinear dynamics of turbochargers

Abstract: A floating-ring bearing (FRB) is composed of a journal, a floating ring and a housing which are separated by two thin oil films. This system is inherently nonlinear and if it is lightly loaded or operated at high speeds, it is prone to the fluid-induced instability. The threshold speed for the instability of a journal bearing with one oil film can be estimated using linearized forces acting in the film. However, the linear analysis of FRB might be problematic because results of such an analysis are usually dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Based on the mathematical model of the above Formulas (1), ( 2), ( 6) and ( 9), the parameters were taken into dimensionless equations, using the standard four-order Runge-Kutta method to perform numerical calculation. The structure parameters of the floating ring bearing-rotor system and floating ring used in this study are shown in Tables 1 and 2, which are derived from references [4,5]. The relative clearance value is the ratio of the oil-film clearance value and the shaft radius in the floating ring bearing.…”
Section: Numerical Simulation and Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the mathematical model of the above Formulas (1), ( 2), ( 6) and ( 9), the parameters were taken into dimensionless equations, using the standard four-order Runge-Kutta method to perform numerical calculation. The structure parameters of the floating ring bearing-rotor system and floating ring used in this study are shown in Tables 1 and 2, which are derived from references [4,5]. The relative clearance value is the ratio of the oil-film clearance value and the shaft radius in the floating ring bearing.…”
Section: Numerical Simulation and Results Analysismentioning
confidence: 99%
“…This work aims to evaluate dimension parameters of FRB in the stability analysis of rotating systems supported by FRB. For the dynamic problems of floating ring bearings, researchers have proposed several simplified linear methods to analyze the dynamic characteristics of bearings [5]. The multi-scale finite-element method is used to establish the dynamic model of floating ring bearings, in which paper, the calculation results are compared with the test results to verify its correctness.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the obtained results for both cases, constant and variable rotor-bearing velocity, show a transient state of the identifiers before the convergence to the estimated values of stiffness and damping bearing parameters. This behavior is due to the sample time used in the numerical simulations of the identifiers for solving the iterated integrals of Equations ( 15) and (24), which utilize the trapezoidal rule. According to Kharab and Guenther [41], this method presents major calculation errors in comparison with other integration methods.…”
Section: Discussionmentioning
confidence: 99%
“…These linear force coefficients are derived from the assumption of small amplitude motions about an equilibrium position [22] and have been used to study the dynamic responses and analyze the stability of rotor systems supported by oil-lubricated tilting-pad bearings, cylindrical bearings and foil bearings, as pointed out in [23] and references within. Recently, Dyk et al [24] presented diverse linearization methods in the stability analysis of rotating systems supported on floating ring bearing (FRBs), demonstrating the usefulness of the linear force coefficients to predict the dynamic behavior of non-linear systems such as turbochargers supported by FRBs.…”
Section: Introductionmentioning
confidence: 99%
“…Peixoto et al [18] studied the influence of temperature on vibration characteristics of the turbocharger rotor system. Dyk et al [19] proposed and analyzed several linearization methods of forces acting on floating ring bearings and proved the nonlinear vibration of the rotor system in combination with campbell diagram. Yongfeng et al [20] used the polynomial chaos expansion method to describe the uncertainty of hollow shaft cracked rotor system.…”
Section: Introductionmentioning
confidence: 99%